Final Endodontic Irrigation with 2% Peracetic Acid: Antimicrobial Activity and Cytotoxicity - Brandão-Neto, Daniel de Oliveira; Mello, João Victor Zebende; Marceliano-Alves, Marilia Fagury Videira; Carvalho Coutinho, Thais Machado de; Marceliano, Eduardo Fagury Videira; Galhardi, Michelle Paiva Weydt; Tavares, Vívian Souza; Muzy Dias, Aline Peçanha; Lins, Renata Ximenes (European Journal of Dentistry, 2021)
Objective The aim of present study was to assess the cytotoxicity and antimicrobial efficacy of 2% peracetic acid (PAA) compared with 5.25% sodium hypochlorite (NaOCl) and 2% chlorhexidine (CHX).Material and Methods For the cytotoxicity test, 100 µl of the tested solutions were added in 12 wells with ECV 304 endothelial cells in each group: NaOCl, CHX, and PAA, in addition to the control group. Each solution was evaluated after 24 hours of contact in four dilutions: 0.2, 0.1, 0.05 and 0.025 through mitochondrial function using MTT colorimetric assay. In the antimicrobial evaluation, 40 dentin blocks 5 mm in length and 0.2 g in weight were incubated with 400 µl of Enterococcus faecalis suspension for 21 days at 37°C. The contaminated samples were divided into three experimental groups within 5 minutes of contact: NaOCl group, CHX group, PAA group, as well as the positive control group. The specimens received treatment and were transferred to a tube with saline for serial dilution of the solution and seeding for isolation and colony forming unit (CFU) count.Statistical Analysis The results obtained were expressed as mean (A570 nm) ± standard deviation (SD) and in a multiple linear regression model and multiple comparisons conducted.Results The antimicrobial evaluation revealed that the NaOCl and CHX groups showed a statistically significant difference compared with the control group (p < 0.001), while the PAA reduced only the CFU growth. It can be concluded that, among the agents tested, PAA expressed greater cell viability, followed by CHX and NaOCl. However, it did not show greater antimicrobial activity in vitro in the mature biofilm of Enterococcus faecalis.
Keywords: chlorhexidine; disinfection; enterococcus faecalis; peracetic acid; sodium hypochlorite